Alginate and hydrotalcite-like anionic clay composite systems: synthesis, characterization and application studies - Mandal, Sujata; Patil, Varsha S.; Mayadevi, S. (Microporous and Mesoporous Materials, 2012)
Hydrotalcite-like anionic clays (Zn/Al and Mg/Al) were intercalated with sodium alginate to form organic-inorganic composite adsorbents for water treatment applications. The synthesized composites were characterized using different characterization techniques viz. XRD, DRIFTS, SEM and surface area/porosity analysis. The adsorption potential of the alginate-clay composites was examined for removal of fluoride ions and Orange II dye from water by adsorption. Our studies revealed that these composites had high adsorption capacity for the adsorption of fluoride and Orange II dye from aqueous solutions. The adsorption capacity of the composites was considerably higher than that of either alginate or clay, used individually. The results indicated that these materials might be useful sorbents for groundwater purification/effluent treatment. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Alginate; Anionic clay; Composite; Fluoride; Orange II dye